Estrés académico y el bienestar psicológico de los estudiantes de la carrera de hotelería y turismo de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2019 - Muñoz Romero, Mercy Diana (2019)
In the present work, it was analyzed how academic stress affects the psychological well-being of a group of university students, breaking down topics such as the causes, symptoms of academic stress, causes and consequences, data that are of vital importance for prevention and respective coping of the same. Anxiety, poor performance, hostility in the environment, and even the desires of desertion are part of the consequences of the presence of academic stress but before the phenomenon are not taken actions until waiting to trigger in depression or when academic stress and which Malignant cancer has affected more than the various areas of development of the individual. The objective of this research revolves around the search for tools to safeguard the psychological well-being of students that focus on competitiveness and the effort to maintain qualifications or other parameters of excellence leave aside the protection of something as basic as health mental without noticing that success depends both on the latter mentioned and on physical health. Within the development of the investigation we will find variations of the stress like symptoms, types and even the physiological answer of the same, consequently with the concepts of psychological well-being where the influence of a determined model of psychological well-being will be denoted where it is intervened in a general way with wide view to the diverse positions of authors who have contributed during the last years.